Researchers' responsibility to uphold Indigenous rights Too often research brings harm to Indigenous peoples - Ignace, Lawrence; Burton, Lauren; Mynott, Sara; Meehan, Mairi; Olson, Erica; Steel, Jade; Ojeda Villarroel, Jaime Andrés; Harper, Sarah; Ramirez, Luisa; Baker, Dana; Sleigh, Laurel; Frenkel, Caitie; et al. (My University, 2023)
The United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), the most comprehensive international human rights instrument concerning Indigenous peoples, was adopted in 2007 by 144 countries to ensure protection of Indigenous rights and self-determination (1). While directed at states, UNDRIP should guide all levels of society. With governments lagging in its implementation, we argue that researchers-at universities, government institutions, consultancies, and elsewhere-have a responsibility to understand and advance these rights. As Indigenous and non-Indigenous researchers with backgrounds and experiences partnering with Indigenous peoples, we reviewed the articles of UNDRIP to identify those relevant to researchers. We summarized these into four themes: self-determination; free, prior, and informed consent; intellectual property; and engagement and learning. These articles provide a starting point for researchers to engage with and become allies in upholding Indigenous rights, in a way that supports Indigenous self-determination and sovereignty now and into the future.
Keywords: None